Decoding national new area development in China: Toward new land development and politics. (April 2019) - Yang, Jun; Li, Yi; Hay, Iain; Huang, Xianjin
Abstract: In recent years, the launch of National New Areas ( guojia xinqu ) has garnered widespread scholarly attention and has been recognized as a new round of rescaling strategies by the Chinese state. While helpful in unpacking the tentative reconfiguration of state spaces, the theory of state rescaling is deficient in its contextualization of the rationalities guiding changes of statehood and its disclosure of the underpinning conflict-ridden processes, which is likely to come to nothing in the end. This article analyses the boom of National New Areas within the broader national context of tightening policy in relation to land development and the central urge to open up new development pathways ( chuangxin fazhan ). Then, drawing on a case study of the Jiangbei National New Area Development in Nanjing, this article critically examines the development and policy innovation process at the local level. By exploring the ongoing projects launched after the central approval of the National New Area, this article argues that what have been triggered by the policy umbrella of National New Area and policy innovation merely rest upon new practices of rural land commodification and development. As a consequence, the crisis of land-centered development is not dealt with effectively. Instead, the continuing development of the built environment through rural land policy innovation is even more deeply embedded in a booming land market, which might place further burden on financialization in the near future. Highlights: Development and policy innovation process at the local level is examined. Policy innovation rests on practices of rural land commodification and development. Crisis of land-centered development is not dealt with effectively. Development of built environment via policy innovation is rooted in the land market. Burdens on financialization in the near future are likely.